Defense Infrastructure: General and Flag Officer Quarters at Fort Shafter, Hawaii; and Fort McPherson, Georgia - INSPECTOR GENERAL DEPT OF DEFENSE ARLINGTON VA (2002)
We conducted an audit of the Services' management controls pertaining to the review and authorization process for maintenance and repair costs for general and flag officer quarters (GFOQ). In addition, we also reviewed the accuracy of FY 2000 maintenance and repair costs. The Office of the Assistant Chief of Staff of the Army for Installation Management is responsible for administering the Army family housing program, to include providing policy and guidance. The Army installation commander is responsible for managing GFOQ operations. This report summarizes the audit of GFOQ maintenance and repair costs at Fort Shafter, Hawaii; and Fort McPherson, Georgia. The U.S. Army Pacific is the major command for Fort Shafter, and the U.S. Army Forces Command is the major command for Fort McPherson. The overall audit objective was to determine the adequacy of management controls for review and authorization of OFOQ costs. This report focuses on annual operations and maintenance costs for specific GFOQs managed by Fort Shafter and Fort McPherson.